Topographical and Morphometrical Observations on the Developing Heart of Chabro Chick Embryos - Pathak, Archana; Gupta, S. K.; Farooqui, M. M.; Prakash, Ajay (Indian Journal of Veterinary Anatomy, 2016)
The topographic and morphometric study was conducted on heart of 42 Chabro chick embryos ranging in age from 1-21 days with two chicks of each day of incubation; divided into 3 age groups viz; group I-IV with 14 chicks in each age group. A curved tubular heart located caudal to the prosencephalon in front of cervical flexure on second day became cone-shaped. By 14th day the heart occupied its definitive (adult type) position in the thoracic cavity. Morphometric data generated on different aspects was analysed. All these parameters showed a progressive growth with advancement in the age of embryo but maximum growth of heart occurred in the embryos of the third age group.